Electrophilic Amination: An Update - Zhou, Zhe; Kürti, László (Synlett, 2019)
In this account, we provide an overview of some recent advances in electrophilic amination methodologies that have been developed in the Kürti group over the last seven years. Our group’s focus has been to develop novel amination methodologies that directly yield N-unprotected amine products.1 Introduction2 Amination of Boronic Acids3 Aziridination of Unactivated Olefins4 Rhodium-Catalyzed C–H Amination of Arenes5 Synthesis of Carbazoles6 Amination of Aryl- and Alkylmetals7 Doubly Electrophilic N-Linchpin Reagents8 Aza-Rubottom Oxidation of Silyl Enol Ethers9 Summary
Keywords: amination; rhodium catalysis; anilines; aminoketones; aziridines